Analisis Wacana Penerapan Kode Etik Jurnalistik dalam Peliputan di Film Korea "The Tunnel" - Febriyola, Dwita Feby; Suprihatin, Suprihatin (DIGICOM : Jurnal Komunikasi dan Media, 2024)
Adherence to the journalistic code of ethics not only demonstrates the integrity and professionalism of a journalist, but also serves as an important foundation in maintaining public trust. good implementation of the journalistic code of ethics can be the foundation for professional and responsible journalistic practices. Through descriptive qualitative method with Teun Van Dijk's Discourse Analysis approach, the analysis structure used in this research includes text (macro structure, superstructure, micro structure), social cognition, and social context. This research aims to analyse how journalists in the coverage of the tunnel collapse disaster are depicted in the film The Tunnel. The results showed that there were criticisms of how journalists violated the South Korean Journalistic Code of Ethics. Particularly article 4 which deals with news and commentary, and article 5 which deals with dignity and privacy. In addition, violations also occur in the standards of practice of journalists based on the code of ethics, such as article 2 on news gathering found in paragraph 2 on natural disaster coverage and paragraph 4 on violations through telephone interviews, and article 3 on news reporting in paragraph 3 regarding the use of sensationalism in news reports. The movie portrays the media as an entity with dual characters: SNC as a media that often violates journalistic ethics and YTN as a media representative that complies with the code of ethics standards.